Decision-making criteria for pesticide spraying considering the bees’ presence on crops to reduce their exposure risk - Decourtye, Axel; Rollin, Orianne; Requier, Fabrice; Allier, Fabrice; Rüger, Charlotte; Vidau, Cyril; Henry, Mickaël (Frontiers in Ecology and Evolution, 2023)
The risk of poisoning bees by sprayed pesticides depends on the attractiveness of plants and environmental and climatic factors. Thus, to protect bees from pesticide intoxication, an usual exemption to pesticide regulations allows for spraying on blooming flowers with insecticides or acaricides when no bees are foraging on crops. Nevertheless, decision-making criteria for farmers to assess the absence of bees on their crops remain under debate. To fill this gap, we present here a review of the literature and an analysis of weather conditions and environmental factors that affect the presence of bees on flowering crops that may be treated with pesticides, with the objective of proposing to farmers a series of decision-making criteria on how and when to treat. We conclude that the criteria commonly considered, such as ambient temperature, crop attractiveness, or distance from field edges, cannot guarantee the absence of forager exposure during pesticide sprays. Nocturnal sprays of pesticides on crops would be the most effective action to help farmers avoid unintentional acute poisoning of bees.